SISTEM INFORMASI PEMESANAN TIKET PADA CV. GLOBAL TRANS SOLUTIONS - Ardiansyah, Teuku (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2020)
This web-based flight ticket booking system development is focused on the problem of web databases and web design that have the aim to provide information about booking tickets online using web media that can facilitate consumers or users of aviation services, where consumers do not need to come to the CV . Global Trans Solutions or aircraft fleet only to make reservations, but with this website can directly order tickets directly via the available web, the author only discusses the problem of web-based Ticket Booking Information System on CV. Global Trans Solutions using PHP and MySQL. The purpose of writing is to find out and design a web-based Ticket Booking Information System on CV. Global Trans Solutions using PHP and MySQL. Data collection needed in writing this research was obtained by two methods, namely literature study relating to the literature of library books and other scientific works, field studies by carrying out interviews, and direct observation of objects related to this research. Web-based Ticket Booking Information System on CV. Global Trans Solutions is carried out by one of the administrative staff and assisted by 2 (two) administrative staff in the field to record and input ticket booking data. From the results of this study, it can be concluded that the web-based Ticket Booking Information System on CV. Global Trans Solutions has followed the procedure and used a computer with Visual PHP and MySQL programming languages ​​as its database.